4-Methyl-1H-1,5-benzodiazepin-2(3H)-one - Khadim Dioukhane; Younas Aouine; Hassane Faraj; Anouar Alami; El Mokhtar Essassi; Hafid Zouihri (IUCrData, 2018)
In the title compound, C10H10N2O, the seven-membered heterocycle displays a half-chair conformation. In the crystal, N—H...O and C—H...O hydrogen bonds link the molecules into chains propagating along the a-axis direction.